STRATEGI PENCITRAAN PERUSAHAAN MELALUI PROGRAM CORPORATE SOCIAL RESPONSIBILITY (STUDI KASUS KEGIATAN MINI NURSERY PROGRAM PT LIPPO CIKARANG, TBK) - Wahyuni, Devi; Yuniarti, Tatik (Makna: Jurnal Kajian Komunikasi, Bahasa, dan Budaya, 2015)
On present the competitive rivalry era, a company is required to establish apositive corporate image on consumers. This positive image will implications on the level of sales and revenue, of company more ever customers satisfaction for customers. Strategic Corporate Social Responsibility (CSR) as a this concept in which PT Lippo Cikarang, Inc. Integrates social and environmental concept implemented by Mini Nursery Program. The purpose of this study to find out how the strategy of corporate social responsibility (CSR) of public relations PT Lippo Cikarang, Inc. in the nursery program (mini-nursery program), to analyze the role of public relations, analyze the  relevant  parties,  and  analyzed  the  mini-nursery  program  as  the  flagship program company. Strategies of CSR by PT Lippo Cikarang, Inc. used a model of planning John M. King is Rope (Research, Objectives, Programs, and Evaluation) on which the initial planning of the CSR activities undertaken. Aplications CSR around Mini Nursery Program activities are conducted with 11 schools located around PT Lippo Cikarang, Inc. product positive image to the increasis in corporate investment as a developer which cares about the environment, it is proved by along the median line which includes the streets and cluster housing in the region looks green